Cost-analysis from real-world REDS study on dalbavancin in inpatient treatment of acute bacterial skin and skin structure infections - Matteo Scortichini; Alessandro Ruggieri; Agnese Cattaneo; Patrizia Mascagni; Paolo Sciattella (Global & Regional Health Technology Assessment)
Introduction: Inpatient treatment of Acute Bacterial Skin and Skin Structure Infections (ABSSSIs) involves a significant economic burden on the healthcare system. The aim of the present analysis was to estimate the expenditure, in terms of direct and indirect healthcare costs, for patients hospitalized with a confirmed diagnosis of ABSSSI, evaluating the impact of dalbavancin, compared to the other Standard of Care of the same IV antibiotic class, analyzed in the REDS study. Methods: The analysis was carried out using data collected as part of the study “Retrospective Effectiveness study of dalbavancin and other Standard of care of the same class IV lipo and glycopeptides) in patients with ABSSSI” (REDS study). In the present analysis, the economic impact of managing patients hospitalized for ABSSSI was estimated by evaluating both the direct healthcare costs relating to hospital and pharmaceutical care and the indirect costs relating to the loss of productivity due to the pathology. Results and Conclusions: The analysis of data from the REDS study made it possible to estimate the economic impact of the management of patients hospitalized for ABSSSI, depending on the treatment received during hospitalization. The results highlighted a reduction in costs for patients treated with dalbavancin, both for direct healthcare costs and indirect costs, over the entire observation period. Again, the reduction increases, reaching statistical significance, and the costs are evaluated from the beginning of the treatment.